2021
DOI: 10.1177/1356336x211053807
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Contextual Model Predicting Change in Out-of-School Physical Activity: A One-Year Longitudinal Study

Abstract: The aim of the current study was to test the long-term predictive validity of the trans-contextual model in accounting for variance in adolescents’ out-of-school physical activity measured by self-report and accelerometer based-devices over a one-year period. Secondary school students ( N  =  265) aged 11 to 15 years completed a three-wave survey on two occasions in time, spanning a one-year interval, measuring perceived autonomy support in physical education (PE), peer and parent autonomy support in leisure-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Using a trans-contextual model of motivation, recent research has found that perceived controlling behaviours might be detrimental to adolescents’ physical activity via the motivations and components of the theory of planned behaviour [ 24 , 25 ]. On the other hand, the trans-contextual model of motivation-based research has also found that autonomy support might have a positive impact on adolescents’ leisure-time physical activities [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using a trans-contextual model of motivation, recent research has found that perceived controlling behaviours might be detrimental to adolescents’ physical activity via the motivations and components of the theory of planned behaviour [ 24 , 25 ]. On the other hand, the trans-contextual model of motivation-based research has also found that autonomy support might have a positive impact on adolescents’ leisure-time physical activities [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it should be considered that the anthropometric information was self-reported and could be inaccurately measured. At the same time, the levels of participants’ PA were measured through a questionnaire and not using objective instruments such as accelerometers; questionnaire-based and accelerometer-based physical activity measures correlate to psychosocial constructs differently [ 47 ]. Thus, accelerometer-based PA measurements should be preferred as they are a more objective way to capture the levels of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…The PA promotion package was developed using a P-process framework, which has been used to design strategic health communication programs worldwide since 1991 and was improved in 2003 [ 29 ]. TPB-based interventions are effective as it has constructs that lead to intention and behaviour [ 23 ]. P-process has five steps: analysis, strategic design, development and testing, implementation and monitoring, evaluation, and replanning.…”
Section: Methodsmentioning
confidence: 99%
“…Interventions based on this theory were found most effective in increasing PA intention and behaviour than other theories [ 16 , 20 , 21 ], and an increase in PA was also found [ 22 ]. There is a link between TPB constructs and change in leisure-time autonomous motivation for PA [ 23 ]. PA effect size was also improved using motivating or rewarding approaches [ 24 ].…”
Section: Introductionmentioning
confidence: 99%